NONPROFIT ORGANIZATION FINANCIAL REPORTING STANDARDS IMPLEMENTATION IN CHURCH - Janie, Dyah N. A.; Yulianti, Yulianti (STIE Pelita Nusantara Semarang, 2023)
This research was conducted in a church as a nonprofit organization operating in the religious field. This study aimed to analyze the application of PSAK No. 45 in financial reporting in a church. This study uses a descriptive qualitative analysis method, which is a study that describes and compares data obtained by observation, interviews, and documentation and analyzes using triangulation techniques. Informant research is based on the principle of appropriateness and adequacy. The basis of the principle of informants in this study was three people. The results showed that the adoption of PSAK No. 45 regarding the financial reporting of nonprofit organizations in the church is not appropriate because the reporting by the church has only been carried out as a whole, not as detailed in PSAK No. 45 regarding the financial reporting of nonprofit organizations.